“The main problem here is one of social behavior”: Intersectional Identities at the Ontario Hospital, Woodstock, 1918-1968 - Bergman, Sarah (Critical Disability Discourses, 2025)
Using the resident case files from the Ontario Hospital, Woodstock, this article looks at the experiences of white and racialized women who were incarcerated between 1918 and 1968. The Ontario Hospital, Woodstock, was one of 20 institutions operated by the province that incarcerated people deemed “feebleminded”. Woodstock’s initial purpose was to house people with epilepsy, and later, tuberculosis. This article aims to respond to the call for more intersectional approaches to disability history. Through the testimonies of doctors and nurses, I interrogate how gender, whiteness, Indigeneity, and age were perceived, constructed, and perpetuated within the walls of institutional life as seen in archival sources. The words of professionals are the only remaining sources, as patient notes and writings have not been archived. The morality and personal views of the professional staff became the basis of treatment and maintained incarceration. Keywords: Disability history, institutionalization, intersectionality, archival research, Ontario